The place of social work in community development with special reference to women participation in Lebowa rural areas - Leseme, Bellinah Mapuleng (My University, 1983)
Refer to the document
Thesis (M. A. (Social Work)) -- University of the North, 1983
Keywords: Social work; Community development; Rural women; Women; Social service